2020
DOI: 10.3390/molecules25071686
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Sensory Characteristics of Virgin Olive Oils During Storage: Interpretation of Their Changes from a Multiparametric Perspective

Abstract: Virgin olive oil is inevitably subject to an oxidation process during storage that can affect its stability and quality due to off-flavors that develop before the oil surpasses its ‘best before’ date. Many parameters are involved in the oxidation process at moderate conditions. Therefore, a multiparametric study is necessary to establish a link between physico-chemical changes and sensory quality degradation in a real storage experiment. In this context, a storage experiment of 27 months was performed for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…During storage under moderate conditions, the panelists detected some changes in the flavor of the oils. As it was highlighted in a previous publication, these changes are explained by the changes in the volatile composition during the storage [ 13 ]. These changes were enough to lead a change in their categories at different time during the storage.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…During storage under moderate conditions, the panelists detected some changes in the flavor of the oils. As it was highlighted in a previous publication, these changes are explained by the changes in the volatile composition during the storage [ 13 ]. These changes were enough to lead a change in their categories at different time during the storage.…”
Section: Resultsmentioning
confidence: 96%
“…Light and temperature, even under moderate conditions, have a great influence on the degradation of VOO [ 6 , 7 , 8 , 9 , 10 ]. Several studies have been focused on the effect of light and temperature upon VOO shelf-life [ 11 , 12 , 13 ]. These studies have highlighted the strong effect of light on the VOO oxidation stability; nevertheless, the response of VOO to moderate light and temperature is highly conditioned by the chemical composition of the oil [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cevik et al (2016) [39] showed a concentration of trans-2-hexenal in the range of 48.45-78.64% for oil from spotted fruits, 32.11-74.52% for oil from purple fruits and 26.73-65.03% for oil from black fruit. This aldehyde is derived from the metabolism of α-linolenic acid through the lipoxygenase (LOX) pathway, which influences the taste of green, pungent, bitter fruity, apple, almond and cut grass [40,41]. Trans-2-hexen-1-ol has green and pungent notes and an odor described as banana-green deriving from the reduction trans-2-hexenal by alcohol dehydrogenase (ADH) [18,20].…”
Section: Aromatic Profilementioning
confidence: 99%
“…Six of the research papers were mainly focused on the sensory aspects related to volatile compounds [ 1 , 2 , 3 , 4 , 5 , 6 ], and another six papers investigated aspects related to processing [ 7 , 8 , 9 ], five papers were more oriented to the quality of the products [ 10 , 11 , 12 , 13 , 14 ], cultivation practice [ 15 ] and storage [ 16 , 17 ], two further papers were more focused on measurement techniques and procedures [ 18 , 19 ]. Lastly, the two review papers reviewed the sensory characteristics (flavour and texture) linked to a physiological disorder of apple, namely watercore [ 20 ] and the influence of ruminant diet on the volatile flavour compounds in cheese [ 21 ].…”
mentioning
confidence: 99%
“…Lobo-Prieto et al [ 17 ] tracked the sensory characteristics of virgin olive oils during storage, showing some disagreements between the sensory assessment and the oxidative stability index analysed by Rancimat.…”
mentioning
confidence: 99%